2017
DOI: 10.2217/fvl-2016-0129
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Building Oncolytic Viruses

Abstract: Oncolytic viruses (OVs) are engineered and/or evolved to propagate selectively in cancerous tissues. They have a dual mechanism of action; direct killing of infected cancer cells cross-primes anticancer immunity to boost the killing of uninfected cancer cells. The goal of the field is to develop OVs that are easily manufactured, efficiently delivered to disseminated sites of cancer growth, undergo rapid intratumoral spread, selectively kill tumor cells, cause no collateral damage and pose no risk of transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 189 publications
(131 reference statements)
0
87
0
1
Order By: Relevance
“…Moreover, expressing therapeutic molecules through OAds provides the unique opportunity to attain targeting tumours using therapeutic agents with unacceptable systemic toxicity profiles 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, expressing therapeutic molecules through OAds provides the unique opportunity to attain targeting tumours using therapeutic agents with unacceptable systemic toxicity profiles 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…OVs are modified or selected to preferentially infect tumor cells. (4) Several OVs preferentially bind to entry receptors disproportionately exhibited on tumor cells, increasing specificity for tumor cell infectivity. (5) Viral entry receptors can also be engineered to target tumor cells.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Initial inoculum size and time to peak viral levels may vary. (4) The inoculum may face significant barriers to intratumoral dissemination such as heterogeneous tumor perfusion and high interstitial pressures. (3, 79)…”
Section: Current Challengesmentioning
confidence: 99%
“…Many genetically modified OVs have been evaluated in clinical trials, as shown in Table 2; such OVs include AdV, VACV, and HSV. OVs mainly genetically modified through the deletion of virulence genes to improve the safety and insertion of foreign genes and improve antitumor efficacy or tumor targeting ability of OVs [77]. The genetic modifications of OVs can be…”
Section: Genetic Modifications Of Ovsmentioning
confidence: 99%